Biased movement drives local cryptic coloration on distinct urban pavements. Issue 1912 (9th October 2019) - Edelaar, Pim; Baños-Villalba, Adrian; Quevedo, David P.; Escudero, Graciela; Bolnick, Daniel I.; Jordán-Andrade, Aída
Abstract : Explanations of how organisms might adapt to urban environments have mostly focused on divergent natural selection and adaptive plasticity. However, differential habitat choice has been suggested as an alternative. Here, we test for habitat choice in enhancing crypsis in ground-perching grasshoppers colonizing an urbanized environment, composed of a mosaic of four distinctly coloured substrates (asphalt roads and adjacent pavements). Additionally, we determine its relative importance compared to present-day natural selection and phenotypic plasticity. We found that grasshoppers are very mobile, but nevertheless approximately match the colour of their local substrate. By manipulating grasshopper colour, we confirm that grasshoppers increase the usage of those urban substrates that resemble their own colours. This selective movement actively improves crypsis. Colour divergence between grasshoppers on different substrates is not or hardly owing to present-day natural selection, because observed mortality rates are too low to counteract random substrate use. Additional experiments also show negligible contributions from plasticity in colour. Our results confirm that matching habitat choice can be an important driver of adaptation to urban environments. In general, studies should more fully incorporate that individuals are not only selective targets (i.e. selected on by the environment), but also selective agents (i.e. selecting their own environments).